IMPLEMENTATION OF COMPETENCE OF PLANNING AND FINANCE BUREAU OF THE SECRETARIAT GENERAL OF THE MPR-RI - Siti Juariah (Universitas prof. Dr. Moestopo (Beragama), 2022)
The Secretariat General of the MPR RI synergistically carries out anticipation to try to increase work productivity by preparing reliable human resources and conditions like this are faced with very basic problems such as not optimal work skills, lack of knowledge development and self-concept in being honest is still not in accordance with expertise as well as job analysis and job specifications that are still not optimal. This study aims to explain the competence of the employees of the Bureau of Planning and Finance of the Secretariat General of the MPR RI in supporting the implementation of MPR tasks and to explain the efforts of the Secretariat General of the MPR RI in developing employee competencies so that they can provide the level of support expected in carrying out MPR constitutional tasks. This research method uses a qualitative approach, with a descriptive study paradigm and an ethnographic approach. The technique used in data collection is through in-depth interviews with key informants, document review and activity observation. The results of the competency research to observe the correctness of the signatures authorized for accountability receipts have been carried out quite well, this is measured from the results of observations of activities described by carrying out tasks, applying standard operating procedures (SOP), causal factors and improvement efforts.